Innovations Developed by Patients and Informal Caregivers for Needs Associated to Rheumatic Diseases - Jacinto, Maria João; Oliveira, Pedro; Canhão, Helena (Frontiers in Medicine, 2021)
Until recently, innovation in healthcare was mainly achieved through the development of new drugs, therapies, and medical devices by big pharma and medtech companies; however, the innovative potential for this field is much broader. The patients and caregivers' role in healthcare is often associated with disease management, demand for their own illness data, and its exchange with other patients. However, the patients and caregivers' capacity to innovate to cope with limitations associated with their health condition is a growing phenomenon and starting to be supported by healthcare stakeholders to achieve a truly patient-centric system. Our previous research has shown that these uncommon innovators can develop a wide range of solutions, from simple adaptations and products to highly technological biomedical devices. In this paper, we present novel solutions developed by rheumatic patients, their caregivers, and collaborators, published on the “Patient Innovation” platform (https://patient-innovation.com/), with a focus on the innovator profile, the need that triggers the innovative process, the type of motivation behind the product, and the products developed. The most significant needs that motivate innovation are the will to increase the level of independence (71%) and to be able to perform daily routine activities (65%). In over 80% of cases, the fact that the market does not fully fulfill the needs felt during daily activities is the main motivation to innovate. It is thus concluded that there is room for innovation in rheumatic diseases with solutions developed by patients and informal caregivers that intend to solve needs that the healthcare market is not covering.